Update in management of paediatric primary spontaneous pneumothorax. (March 2022) - Lieu, Nathan; Ngo, Peter; Chennapragada, S. Murthy; Fitzgerald, Dominic A.; Karpelowsky, Jonathan; Pandit, Chetan; Selvadurai, Hiran; Robinson, Paul D.
Abstract: Paediatric spontaneous pneumothorax (PSP) management continues to lack paediatric-specific guideline recommendations. There have been increasing reports of paediatric retrospective case studies supplemented by important well designed RCT (predominantly) adult studies. Taken together, these suggest that conservative management may have an increasing role to play in the management of PSP and that aspiration may have limited utility as a first line intervention. Our local experience, as part of a multicentre retrospective analysis and subsequent audit of management since, corroborates recent published data: it highlights an increasing trend towards conservative management in spontaneous pneumothorax with similar rates of recurrence, compared to intervention, and low use of aspiration with similarly low success rates. We have therefore updated our local practice guidelines and share these with readers. Specifically, we have removed aspiration in the management of primary spontaneous pneumothorax and reserved intervention for children who are clinically unstable or show evidence of increasing air leak irrespective of pneumothorax size. Whilst the success of this change in clinical practice will need to be reviewed in the next 5–10 years, the overall low incidence of the condition, demands a multicentre, and probably multinational, collaborative approach to allow the best chance of obtaining definitive evidence to guide clinical paediatric management.